2018
DOI: 10.2147/ijn.s163858
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted delivery of doxorubicin to enhance antitumor activity with HER-2 peptide-mediated multifunctional pH-sensitive DQAsomes

Abstract: IntroductionMultidrug resistance (MDR) of breast cancer is the major challenge to successful chemotherapy while mitochondria-targeting therapy was a promising strategy to overcome MDR.Materials and methodsIn this study, HER-2 peptide-PEG2000-Schiff base-cholesterol (HPSC) derivate was synthesized successfully and incorporated it on the surface of the doxorubicin (DOX)-loaded dequalinium (DQA) chloride vesicle (HPS-DQAsomes) to treat drug-resistant breast cancer. Evaluations were performed using human breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“… 55,56 Using the antibody as a template, Shi et al synthesized an HER-2 peptide analog, sequence YCDGFYACYMDV, which showed increased tumoral delivery of doxorubicin-loaded and pH-sensitive liposomes toward multidrug-resistant MCF-7 breast cancer cells. 56 In this study, they showed a strong increase in mitochondrial localization compared to other organelles, which is important for increasing mitochondrial-driven apoptosis. Zahmatkeshan and coworkers also studied HER2 targeting with a different peptide and Anti-HER2/neu peptide (AHNP) with sequence FCDGFYACYADV, this time to improve localization of doxorubicin-loaded PEGylated liposomes.…”
Section: Receptor-targeting Peptide Ligandsmentioning
confidence: 52%
“… 55,56 Using the antibody as a template, Shi et al synthesized an HER-2 peptide analog, sequence YCDGFYACYMDV, which showed increased tumoral delivery of doxorubicin-loaded and pH-sensitive liposomes toward multidrug-resistant MCF-7 breast cancer cells. 56 In this study, they showed a strong increase in mitochondrial localization compared to other organelles, which is important for increasing mitochondrial-driven apoptosis. Zahmatkeshan and coworkers also studied HER2 targeting with a different peptide and Anti-HER2/neu peptide (AHNP) with sequence FCDGFYACYADV, this time to improve localization of doxorubicin-loaded PEGylated liposomes.…”
Section: Receptor-targeting Peptide Ligandsmentioning
confidence: 52%
“…As ROS also play important roles in normal physiology, chronic inhibition of ROS may result in off-target responses and side effects. Previous attempts have been done to increase mitochondria targeting of therapeutic drugs, mostly using conjugation of agents to various compounds (Wolf et al, 1997, Wolf et al, 2000), including nanoparticles (Hidaka et al, 2017; Akhmadishina et al, 2018; Battogtokh et al, 2018; Mattarei et al, 2018; Shi et al, 2018). We have previously shown that high enzymatic activities of the peptidases APA and γ-GT in diseased human and rat kidneys may represent targets to develop prodrug therapeutics (Juillerat-Jeanneret et al, 1992; Juillerat-Jeanneret et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our current findings revealed the role of RASSF6 as a positive regulator of chemosensitivity. It has been reported that mitochondria are involved in apoptosis, and chemotherapeutic drugs induce apoptosis through mitochondria-dependent pathways 810. The JC-1 staining assay was first performed to examine Δψm to characterize the role of RASSF6 on mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%